Utilization of cervical cancer screening among migrants and non-migrants in Germany: results from a large-scale population survey - Patrick Brzoska; Tuğba Aksakal; Yüce Yilmaz-Aslan (BMC, 2020)
Abstract Background Studies from European and non-European countries have shown that migrants utilize cervical cancer screening less often than non-migrants. Findings from Germany are inconsistent. This can be explained by several limitations of existing investigations, comprising residual confounding and data which is restricted to only some regions of the country. Using data from a large-scale and nationwide population survey and applying the Andersen Model of Health Services Use as the theoretical framework, the aim of the present study was to examine the role that different predisposing, enabling and need factors have for the participation of migrant and non-migrant women in cervical cancer screening in Germany. Methods We used data from the 'German Health Update 2014/2015' survey on n = 12,064 women ≥20 years of age. The outcome of interest was the participation in cancer screening (at least once in lifetime vs. no participation). The outcome was compared between the three population groups of non-migrants, migrants from EU countries and migrants from non-EU countries. We employed multivariable logistic regression to examine the role of predisposing, enabling and need factors. Results Non-EU and EU migrant women reported a lower utilization of cervical cancer screening (50.1 and 52.7%, respectively) than non-migrant women (57.2%). The differences also remained evident after adjustment for predisposing, enabling and need factors. The respective adjusted odds ratios (OR) for non-EU and EU migrants were OR = 0.67 (95%-CI = 0.55-0.81) and OR = 0.80 (95%-CI = 0.66-0.97), respectively. Differences between migrants and non-migrants were particularly pronounced for younger age groups. Self-rated health was associated with participation in screening only in non-migrants, with a poorer health being indicative of a low participation in cancer screening. Conclusions The disparities identified are in line with findings from studies conducted in other countries and are indicative of different obstacles this population group encounters in the health system. Implementing patient-oriented health care through diversity-sensitive health services is necessary to support informed decision-making.